Pengaruh Penggunaan Video Animasi Berbasis STEM Berbantuan Web terhadap Kemampuan Berpikir Kreatif Siswa pada Materi Desain Grafis di SMKN 1 Kota Bima - Bayu Rawanda; Suharti Suharti; Lisda Ramdhani (STKI Harapan Bima, 2025)
Technological advancements in education have opened opportunities to implement innovative and effective learning media. This study aims to examine the effect of using STEM-based (Science, Technology, Engineering, Mathematics) animated videos supported by a web platform on students’ creative thinking skills in graphic design subjects at SMKN 1 Kota Bima. The research employed a quasi-experimental design with a nonequivalent control group, involving both an experimental group and a control group. The research subjects consisted of 60 eleventh-grade students majoring in Graphic Design, with 30 students in the experimental group and 30 in the control group. Data were collected through creative thinking skill tests, questionnaires, and observations. The results showed a significant difference in creative thinking skills between students who used the STEM-based animated video and those who received conventional instruction, with an average increase of 28% in the experimental group. This media provided a more engaging and interactive learning experience and effectively facilitated students’ understanding of graphic design concepts in an innovative and enjoyable way. It is concluded that the use of web-assisted STEM-based animated videos has a positive and significant effect on students' creative thinking skills in graphic design learning at SMKN 1 Kota Bima.